SUBJECT-VERB AGREEMENT AND ASPECT IN MUNA LANGUAGE - La Ode Nggawu (Humaniora, 2013)
The article examines subject-verb agreement and aspect in Muna language. The data of this study were collected through observation and note-taking and analyzed syntactically. The results of the study show that (1) Muna language has subject markers attached to predicates; (2) the subject markers are (a) /a/, /ae/, /ao/ (for subject ‘I’), (b) /da/, /dae/, /dao/ (for subject ’we’ for 2 persons), (c) /da- -mu/, /dae- -mu/, /dao- mu/ (for subject ‘we’ for more than 2 persons), (d) /o/, /ome/, /omo/ (for subject ‘you’ singular), (e) /o- -mu/, /ome- -mu/, /omo- mu/ (for subject ‘you’ plural), (f) /no/, /ne/ (subject ‘she/he’), and (g) /do/, /de/ (for subject ‘they’); (3) variation for each subject marker is influenced by predicate types such as transitive, intransitive, or adjective; (4) Muna language uses infix /-um-/ to express the event in the future, nando to express a progressive event, and suffix /mo-/ or lexical padamo to express the event in the past; (5) Muna language differentiates the concept of aspect in negative sentences from that in positive sentences; it uses miina ‘not’ to express a negative statement in the past, and the prefix /pa:/ to express a negative statement in the future; and (6) Muna language has aspect markers.